2012
DOI: 10.3109/19401736.2011.643876
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of threeOmpokspecies using mitochondrialCOIgene

Abstract: A DNA-based barcode identification system that is applicable to all animal species will provide a simple, universal tool for the identification of fish species. The barcode system is based on sequence diversity in subunit 1 cytochrome c oxidase (COI) gene. Identification and characterization of fish species based on morphological characters are sometimes found to be erroneous and environmentally affected. There are no studies on the genus Ompok in India at molecular level and species identification of the Ompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The concept of DNA barcoding has been empirically supported and used in various studies on different phyla (Hebert et al, 2003;Hebert et al, 2004aHebert et al, , 2004bHogg & Hebert, 2004;Moritz & Cicero, 2004), leading to the development of a standard screening of species diversity that allows taxonomists to accelerate the identification process of fishes (Keskin & Atar, 2013;Lakra et al, 2011;Landi et al, 2014;Ward et al, 2005). Furthermore, since proper identification is crucial for management and trade, this DNAbased barcode provides a simple universal tool for the identification of fish species and products (Lakra et al, 2011;Malakar et al, 2012;Smith et al, 2008). DNA barcoding not only applies for fish species identification, but also for fish product examination (fillets, fins, fragments, canned fish, dried fish, mixtures), conservation of threatened and endangered species, identification of fish eggs and larvae, identification of prey items in stomach contents (Soininen et al, 2009), identification of new species, population structure assessment, phylogenetics and biodiversity assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of DNA barcoding has been empirically supported and used in various studies on different phyla (Hebert et al, 2003;Hebert et al, 2004aHebert et al, , 2004bHogg & Hebert, 2004;Moritz & Cicero, 2004), leading to the development of a standard screening of species diversity that allows taxonomists to accelerate the identification process of fishes (Keskin & Atar, 2013;Lakra et al, 2011;Landi et al, 2014;Ward et al, 2005). Furthermore, since proper identification is crucial for management and trade, this DNAbased barcode provides a simple universal tool for the identification of fish species and products (Lakra et al, 2011;Malakar et al, 2012;Smith et al, 2008). DNA barcoding not only applies for fish species identification, but also for fish product examination (fillets, fins, fragments, canned fish, dried fish, mixtures), conservation of threatened and endangered species, identification of fish eggs and larvae, identification of prey items in stomach contents (Soininen et al, 2009), identification of new species, population structure assessment, phylogenetics and biodiversity assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that the partial COI gene sequence of fin clips and muscle tissue can be used as a diagnostic molecular marker for identification and resolution of taxonomic ambiguity of Ompok species [38]. Other study showed that the genes of cytochrome oxidase…”
Section: Introduction *mentioning
confidence: 65%
“…There were between 1 and 12 variable nucleotide sites among the haplotypes, 6 of which differed by transitional substitutions, 3 by transversional changes and 3 insertion/deletions (Table 2). Transitional changes are commonly found in animal mitochondrial genomes compared to tranversional changes (Malakar et al, 2009;FiĆĄer Pečnikar & Buzan, 2013). In addition, 9 variable sites with 2 parsimony informative sites were detected.…”
Section: Resultsmentioning
confidence: 99%